Dynamics of bioelements during leaf decomposition in three forest ecosystems of semiarid climate in the Duero Basin (Arid Soil Research and Rehabilitation, 1995)
The dynamics of bioelements lost during leaf litter decomposition were experimentally determined in three forest ecosystems located in a semiarid zone of the Duero Basin, Province of Zamora, Spain, during 2 years. The three ecosystems were a climax Quercus rotundifolia (evergreen oak) woodland, a paraclimax Pinus pinea (stone pine) forest, and a disclimax P. pinaster (maritime pine) forest. The total content of bioelements found in the litter was low in relation to other forest ecosystems: 27, 14, and 8 kg N ha?1 in Q. pyrenaica, P. pinea, and P. pinaster, respectively; 17, 10, and 9 kg Ca ha?1, respectively; about 2 kg P ha?1, 4 kg K ha?1, and 5 kg Mg ha?1 in the three forests. The Q. rotundifolia woodland potentially returns a greater amount of N and Ca than both Pinus forests. An in situ litter bag method was used for the determination of dynamics of the decomposing leaves. A progressive loss of C, P, and Mg in the decomposing oak leaves and pine needles, and a sharp loss of K were observed; by comparison, a tendency to maintain N and Ca was seen. Pinus pinaster forest had the lowest annual N and P return.
doi: 10.1080/15324989509385911